UPTAKE, TRANSLOCATION AND PERSISTANCE OF CARBENDAZIM IN COCONUT IN RELATION TO CONTROL OF STEM BLEEDING DISEASE - ANIL KUMAR; K.K.N. Nambiar; S.R. VOLETI (International Coconut Community, 1992)
Uptake, translocation and persistance of carbendazim in coconut in relation to control of stem bleeding caused by Thielaviopsis paradoxa was studied. The fungicide when applied through a single root @ 10g Bavistin/palm, was detected up to 2m height in the trunk of treged palms on feeding side, whereas no fungicide was detected from remaining three sides. In the former case, the furigicide accumulated in sufficient concentrations to arrest the internal decay for six months. The residues detected in nut water from nuts of different maturity from treated adult palms (20 ‑ 25 yrs.) were within safe limits.